(untitled) (Journal of Forensic Medicine & Toxicology, 2026)
Electrocution is a significant but under-monitored public health concern in low- and middle-income countries. This retrospective descriptive study analyzed 60 fatal electrocution autopsies performed at a tertiary care hospital between 2022 and 2024. Cases were selected through purposive sampling based on predefined inclusion criteria. Data included victim demographics, seasonal variations, voltage source, manner of death, and characteristic autopsy findings. Young adult males constituted 92% of victims, with most deaths occurring during summer and monsoon seasons. Low-voltage household electricity accounted for two-thirds of cases. Characteristic external findings included dermo-epidermal burns (75%), entry–exit wounds (48%), and crocodile-skin patterned arc lesions (13%). Nearly all deaths (98%) were accidental. The study highlights the preventable nature of electrocution fatalities and the urgent need for improved domestic electrical safety, infrastructural regulation, and seasonal public health interventions.